Properties of Thermoplastic Starch/Poly(Lactic Acid) Blends - Huang, Xue-Cheng (My University, 2005)
High amylose cornstarch, normal cornstarch and waxy cornstarch were plasticized using water and glycerol as plasticizers in a Haake Rheomix 3000 batch mixer. A two-level factorial experiment design was used to investigate the effects of processing conditions and the water/glycerol ratio on the mechanical properties of the thermoplastic starches. The significances of factors (processing temperature, time, roller rolling rate and ratio of water to glycerol) on the mechanical properties were evaluated. The morphology, thermal properties, average molecular weight and molecular weight distribution of the thermoplastic starches were analyzed using scanning electron microscopy (SEM), differential scanning calorimetry (DSC) and high performance size exclusion chromatography (HPSEC). The mechanical properties and rheological properties of the materials were measured using an Instron tensile testing machine and a Rosand capillary rheometer. The thermoplastic starches were further blended with poly(lactic acid)(PLA) at different composition ratios. The morphology, thermal properties, molecular weight and molecular weight distribution of the thermoplastic starch/PLA blends were analyzed using SEM, DSC, HPSEC. Mechanical and rheological properties of the blends were investigated using the same methods as those used in the investigation of thermoplastic starches. The effects of amylose content in the starches, composition (starch/plasticizer ratio, water/glycerol ratio, starch/PLA ratio), molding methods and molding temperature on structure and properties of thermoplastic starches and thermoplastic starch/PLA blends were also investigated and compared. A power law model and a cross model were used to fit the experimental rheological data of the thermoplastic starches and the thermoplastic starch/PLA blends. The thermoplastic normal starch with starch/plasticizer ratio of 2/1 (wt/wt%) shows a tensile strength of 2.81 MPa, a modulus of 55.09MPa and an elongation at break of 76.0%. The post-extruded thermoplastic normal starch/PLA blend with the starch/PLA ratio of 50/50 (wt/wt) and the starch/plasticizer ratio of 2/1(wt/wt) exhibits a tensile strength of 15 MPa, a modulus of 926 MPa and an elongation at break of 6%.
Keywords: thermoplastic; starch; lactic acid; properties